Silicon-graphite-carbon composite material for negative electrode of lithium ion battery and preparation method of silicon-graphite-carbon composite material

Through the use of silicon graphite carbon composite materials, the problem of poor durability of pure silicon negative electrode materials is solved. By forming a porous carbon skeleton network structure and carbon shell layer, the electrochemical stability and specific capacity of lithium-ion batteries are improved, and the battery is extended service life.

CN119252882APending Publication Date: 2025-01-03NANJING GUOXUAN NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411308324.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Pure silicon negative electrode materials have poor durability in lithium-ion batteries and are easy to powder, which cannot meet the requirements of high lithium storage performance.

Method used

Silicon graphite carbon composite material is used to form a porous carbon frame network structure and carbon shell layer through the combination of nano-scale silicon powder, expanded graphite and organic carbon source, which buffers the volume expansion of silicon and improves conductivity.

Benefits of technology

It improves the electrochemical stability and specific capacity of the negative electrode of lithium-ion battery, extends the service life of the battery, and enhances the cycling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005049915900000121
    Figure BDA0005049915900000121
  • Figure BDA0005049915900000131
    Figure BDA0005049915900000131
  • Figure HDA0005049915920000011
    Figure HDA0005049915920000011
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, and particularly discloses a silicon-graphite-carbon composite material for a negative electrode of a lithium ion battery and a preparation method of the silicon-graphite-carbon composite material. The silicon graphite carbon composite material comprises the following raw materials in parts by weight: 10-50 parts of expanded graphite, 15-27 parts of silicon powder with the average particle size of 30-120 nanometers, 35-63 parts of an organic carbon source and 0.3-1 part of a surfactant. The silicon-graphite-carbon composite material comprises a porous carbon skeleton network structure, silicon powder particles and a carbon shell layer, the silicon powder particles are embedded in the porous carbon skeleton network structure, and the carbon shell layer wraps the surfaces of the porous carbon skeleton network structure and the silicon powder particles. The preparation method is beneficial to improving the electrochemical stability and the specific capacity of the battery, so that the durability of the lithium ion battery negative electrode material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a silicon-graphite-carbon composite material for a negative electrode of a lithium-ion battery and a preparation method thereof. Background Art

[0002] After 1970, lithium batteries made of metallic lithium as negative electrode materials were commercially used. However, in actual use, it was found that when metallic lithium negative electrode materials were charged and discharged, lithium dendrites were easily generated to pierce the battery's diaphragm, causing the positive and negative electrodes to contact, forming a short circuit and thus an explosion. With the development of science and technology and the in-depth research, the most commercially promising lithium battery today is the lithium-ion battery made of carbon material as the negative electrode material, which has the characteristics of relatively safe charging and discharging, excellent cycle performance, high specific capacity, stable operating voltage, long service life and low pollution.

[0003] In the related technology, the theoretical lithium storage capacity of carbon materials can reach 372mAh / g, but with the growing needs of people, the requirements for lithium storage performance of lithium-ion batteries are getting higher and higher. Lithium-ion batteries made of carbon materials as negative electrode materials can no longer meet people's needs. Silicon has a theoretical lithium storage capacity of 4200mAh / g and rich mineral resources, so it has attracted great attention. Scientists apply silicon materials to negative electrode materials to improve the lithium storage performance of negative electrode materials.

[0004] However, the volume of pure silicon negative electrode materials will become several times the original size during the process of lithium insertion and extraction. Moreover, silicon materials are easily pulverized at high temperatures, which makes the durability of pure silicon negative electrode materials poor, limiting the further development of silicon materials in negative electrode material applications. Summary of the invention

[0005] In order to improve the durability of negative electrode materials of lithium-ion batteries, the present application provides a silicon-graphite-carbon composite material for negative electrodes of lithium-ion batteries and a preparation method thereof.

[0006] In a first aspect, the present application provides a silicon-graphite-carbon composite material for a negative electrode of a lithium-ion battery, which adopts the following technical solution:

[0007] A silicon-graphite-carbon composite material for a lithium-ion battery negative electrode comprises the following raw materials in parts by weight: 10-50 parts of expanded graphite, 15-27 parts of silicon powder with an average particle size of 30-120 nanometers, 35-63 parts of an organic carbon source, and 0.3-1 part of a surfactant.

[0008] By adopting the above technical solution, compared with ordinary silicon materials, since the size of silicon powder particles is reduced to the nanoscale, the size effect causes the specific surface area and surface energy of silicon particles to change, and the solid electrolyte interface film of silicon powder particles is also more stable, which helps to reduce the possibility of pulverization of silicon particles at high temperatures. Since expanded graphite has a unique lamellar structure, it can expand 150-300 times after high-temperature expansion and form a porous carbon skeleton network structure, and silicon powder can be embedded in the porous carbon skeleton network structure. After high-temperature heat treatment, the organic carbon source will form a carbon shell layer and coat the silicon powder and the porous carbon skeleton network structure. Surfactants can reduce surface tension and help improve the uniform doping effect.

[0009] The above raw materials are used to help obtain a silicon-graphite-carbon composite material with a built-in porous carbon skeleton network structure, in which silicon powder particles are embedded and coated with a surface carbon shell. The carbon shell can not only buffer the volume expansion of silicon through its good elasticity and toughness, but also provide additional electronic conduction paths, enhance the conductivity of the material, and thus improve the charge and discharge performance of the electrode. In addition, the carbon shell can also reduce the charge migration impedance of silicon, which is conducive to the rapid deintercalation of lithium ions and further optimizes the kinetic performance of the electrode. However, only the carbon shell is not enough to support the structure. The porous carbon skeleton network structure formed by expanded graphite is not only structurally stable and has certain flexibility, but also can support silicon powder particles and carbon shells, and has high electronic conductivity, large lithium ion diffusion coefficient and unique porous structure, which is conducive to the repeated insertion-extraction of lithium ions, so that the expansion of silicon can be better buffered. Therefore, the use of the silicon-graphite-carbon composite material of the present application as the negative electrode material of the lithium ion battery helps to improve the electrochemical stability and specific capacity of the battery, thereby improving the durability of the negative electrode material of the lithium ion battery.

[0010] In a specific embodiment, the organic carbon source is one or a combination of sucrose, starch or cellulose.

[0011] By adopting the above technical solution, sucrose, starch or cellulose can form a carbon shell after high-temperature heat treatment. Moreover, the formed carbon shell has good elasticity, toughness and conductivity, which helps to reduce the pulverization of silicon powder and buffer the volume expansion of silicon.

[0012] In a specific embodiment, the organic carbon source comprises natural rubber and urea in a weight ratio of 10:(0.5-2).

[0013] By adopting the above technical solution, the carbon content of natural rubber is as high as 92-95%, and it is easy to form a graphitized structure after pyrolysis. Urea can decompose and release nitrogen atoms during pyrolysis, which are incorporated into the carbon structure to change its electronic properties. Therefore, a mixture of natural rubber and urea is used as an organic carbon source to form a carbon shell layer with good elasticity, toughness and conductivity, which helps to reduce the pulverization of silicon powder and buffer the volume expansion of silicon.

[0014] In a specific embodiment, the organic carbon source further includes lithium bromide, and the weight ratio of the natural rubber to the lithium bromide is 10:(0.02-0.1).

[0015] Lithium bromide can play a catalytic role in the pyrolysis process, promoting the graphitization process of the carbon structure, thereby further improving the conductivity of the carbon shell.

[0016] In a specific possible implementation scheme, the silicon-graphite-carbon composite material for the negative electrode of a lithium-ion battery includes a porous carbon skeleton network structure, silicon powder particles and a carbon shell layer, wherein the silicon powder particles are embedded in the porous carbon skeleton network structure, and the carbon shell layer is wrapped around the surface of the porous carbon skeleton network structure and the silicon powder particles.

[0017] In a second aspect, the present application provides a method for preparing a silicon-graphite-carbon composite material for a negative electrode of a lithium-ion battery, using the following technical solution:

[0018] A method for preparing a silicon-graphite-carbon composite material for a lithium-ion battery negative electrode comprises the following steps:

[0019] Primary mixing: adding silicon powder, organic carbon source and surfactant into water and mixing evenly to obtain raw material liquid;

[0020] Secondary mixing: adding expanded graphite to ethanol, mixing evenly to obtain a graphite solution, ultrasonically dispersing the graphite solution, and then mixing evenly with the raw material solution to obtain a mixed solution;

[0021] Drying: heating the mixed liquid to remove water and ethanol from the mixed liquid to obtain a mixed solid, and drying the mixed solid to obtain a solid block;

[0022] Heat treatment: heat the solid block to 200-300°C in an inert atmosphere, keep it warm for 1-3 hours, heat it to 550-650°C, keep it warm for 2-5 hours, and obtain a silicon-graphite-carbon composite material.

[0023] By adopting the above technical scheme, the present application mixes silicon powder, organic carbon source and surfactant in water, which helps silicon powder and organic carbon source to be uniformly dispersed in advance, and then mixed with graphite solution, silicon powder and organic carbon source can enter the lamellar structure of expanded graphite. In the heat treatment step, the carbon shell layer formed by the organic carbon source is helpful to wrap the silicon powder and be embedded in the porous carbon skeleton network structure, so as to achieve the volume expansion effect of buffering silicon and reduce the effect of silicon powderization. Moreover, using the above preparation method, the prepared silicon-graphite carbon composite material is uniform in material, high in specific capacity, good in conductivity, has excellent electrochemical stability, and is applied to the negative electrode of lithium batteries, which can improve the cycle performance and specific capacity of lithium batteries.

[0024] In a specific embodiment, in the heat treatment step, the heating rate is 2-10° C. / min.

[0025] By adopting the above technical solution, the present application has found through experiments that when the heating rate is too large or too small, the specific capacity of the prepared silicon-graphite-carbon composite material will decrease, and the cycle performance will deteriorate. This may be because the heating rate is too large or too small, which will cause the speed of the organic carbon source to form a carbon shell layer and the speed of the expanded graphite to expand inconsistently, making it difficult to form a composite material in which organic silicon is embedded in a porous carbon skeleton network structure and the carbon shell wraps silicon powder and a porous carbon skeleton network structure. Therefore, it will cause the specific capacity to decrease and the cycle performance to deteriorate. When the heating rate is controlled at 2-10°C / min in the present application, the prepared silicon-graphite-carbon composite material has significantly excellent cycle performance and specific capacity.

[0026] In a third aspect, the present application provides a method for preparing a silicon graphite carbon negative electrode, using the following technical solution:

[0027] A method for preparing a silicon-graphite-carbon negative electrode comprises the following steps:

[0028] The silicon-graphite-carbon composite material and the conductive agent are mixed to obtain a conductive mixture, the binder is dissolved in N-methylpyrrolidone to obtain a binder solution, and the conductive mixture and the binder solution are uniformly mixed to obtain a slurry;

[0029] The slurry is coated on a copper foil, dried, stamped, compacted, weighed and dried again to obtain a silicon-graphite-carbon negative electrode.

[0030] In a specific embodiment, the conductive agent is a SP-Li conductive agent.

[0031] By adopting the above technical solution, the SP-Li conductive agent has good synergy in the electrode at a lower addition amount, which can effectively improve the battery cycle capacity and cycle life.

[0032] In a specific embodiment, the binder is polyvinylidene fluoride, aqueous sodium carboxymethyl cellulose or styrene-butadiene rubber.

[0033] By adopting the above technical solution, polyvinylidene fluoride is a high-strength, chemically resistant binder that can effectively tightly bond the active material in the negative electrode material with the conductive agent, current collector, etc. to form a stable electrode structure. Moreover, it can maintain stable bonding performance during the battery charging and discharging process, thereby extending the service life of the battery. Its good mechanical strength can also effectively prevent the electrode from cracking or falling off during preparation and use. Aqueous sodium carboxymethyl cellulose can form a uniform network structure, firmly bond the active material and the conductive agent to the current collector, and can also significantly improve the slurry stability of the electrode, making the slurry more uniform during the coating process, thereby improving the consistency of the electrode. Styrene-butadiene rubber can provide good elasticity and bonding force, ensure close contact between the active material and the current collector, and help enhance the flexibility and impact resistance of the electrode, thereby improving the safety and reliability of the battery during use.

[0034] In summary, this application has the following beneficial effects:

[0035] 1. The silicon-graphite-carbon composite material of the present application is used as a negative electrode material for a lithium-ion battery, which helps to improve the electrochemical stability and specific capacity of the battery, thereby improving the durability of the negative electrode material of the lithium-ion battery.

[0036] 2. In the present application, a mixture of natural rubber and urea is preferably used as the organic carbon source, which can form a carbon shell layer with good elasticity, toughness and conductivity, help reduce the pulverization of silicon powder and buffer the volume expansion of silicon.

[0037] 3. The method of the present application prepares a silicon-graphite-carbon composite material with uniform material, high specific capacity, good conductivity, and excellent electrochemical stability. It is applied to the negative electrode of a lithium battery to improve the cycle performance and specific capacity of the lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is the first charge and discharge capacity diagram of the CR2032 button battery assembled with the silicon graphite carbon negative electrode of Examples 1-5.

[0039] Figure 2 It is a graph of the 50-cycle reversible specific capacity of the CR2032 button battery assembled with the silicon-graphite-carbon negative electrode of Examples 1-5.

[0040] Figure 3 This is the AC impedance spectrum of the CR2032 button cell assembled with the silicon-graphite-carbon negative electrode of Examples 1-5 after 50 cycles.

[0041] Figure 4This is a SEM image of the silicon-graphite-carbon composite material for a negative electrode of a lithium-ion battery of Example 1. DETAILED DESCRIPTION

[0042] The following is combined with Figure 1-4 , Examples and Comparative Examples further illustrate the present application in detail.

[0043] Example

[0044] Example 1

[0045] This embodiment provides a silicon-graphite-carbon composite material for a negative electrode of a lithium-ion battery, using the following raw materials: 30 g of expanded graphite, 21 g of silicon powder with an average particle size of 30 nanometers, 49 g of sodium carboxymethyl cellulose, and 0.5 g of hexadecyltrimethylammonium bromide.

[0046] The preparation method of the silicon-graphite-carbon composite material for the negative electrode of a lithium-ion battery comprises the following steps:

[0047] According to the proportion, silicon powder and sodium carboxymethyl cellulose are added into sufficient amount of water, stirred evenly, and then cetyl trimethyl ammonium bromide is added, and ultrasonication is performed until the dispersion is evenly dispersed to obtain a raw material liquid.

[0048] According to the proportion, the expanded graphite is added to a sufficient amount of ethanol, and the mixture is uniformly mixed to obtain a graphite solution. The graphite solution is then ultrasonicated at 40 kHz for 1 hour, and then added to the raw material solution, and the mixture is uniformly stirred to obtain a mixed solution.

[0049] The mixed solution was heated to 60°C, stirred for 1 hour while keeping warm, and then heated to 90°C and stirred continuously until the water and ethanol in the mixed solution were completely evaporated to obtain a mixed solid. The mixed solid was then dried in a forced air drying oven at 105°C for 30 hours to obtain a solid block.

[0050] The solid block was transferred to a porcelain boat, placed in a tubular furnace and introduced into an inert atmosphere for heat treatment. The temperature was raised to 250°C at a rate of 5°C / min, and then kept warm for 2 hours. The temperature was then raised to 600°C at a rate of 5°C / min, and then kept warm for 3.5 hours to obtain a silicon-graphite-carbon composite material.

[0051] This embodiment also provides a method for preparing a silicon-graphite-carbon negative electrode, which comprises the following steps:

[0052] Weigh 0.95 g of silicon-graphite-carbon composite material, 0.01 g of SP-Li conductive agent, 0.004 g of aqueous sodium carboxymethyl cellulose and 0.036 g of N-methylpyrrolidone.

[0053] The silicon-graphite-carbon composite material and the SP-Li conductive agent are mixed, and stirred in a dry powder state for 1.5 hours until uniform to obtain a conductive mixture, and aqueous sodium carboxymethyl cellulose is dissolved in N-methylpyrrolidone to obtain a binder solution. Then, the conductive mixture and the binder solution are mixed, and stirred for 4 hours until uniform to obtain a slurry.

[0054] The slurry was evenly coated on the copper foil cleaned with ethanol, dried in a forced air drying oven at 80°C for 3 hours, and then dried in a vacuum drying oven at 120°C for 16 hours to obtain the electrode. The electrode was punched into a circular electrode sheet with a diameter of 13 mm, compacted under a tablet press, weighed, and then placed in a vacuum drying oven for secondary drying to obtain a silicon graphite carbon negative electrode.

[0055] Example 2

[0056] The only difference between this embodiment and embodiment 1 is that the silicon-graphite-carbon composite material used for the negative electrode of the lithium-ion battery adopts the following raw materials: 20 g of expanded graphite, 24 g of silicon powder with an average particle size of 30 nanometers, 56 g of sodium carboxymethyl cellulose, and 0.6 g of hexadecyltrimethylammonium bromide.

[0057] Example 3

[0058] The only difference between this embodiment and embodiment 1 is that the silicon-graphite-carbon composite material for the negative electrode of the lithium-ion battery uses the following raw materials: 10 g of expanded graphite, 27 g of silicon powder with an average particle size of 30 nanometers, 63 g of sodium carboxymethyl cellulose, and 1 g of hexadecyltrimethylammonium bromide.

[0059] Example 4

[0060] The only difference between this embodiment and embodiment 1 is that the silicon-graphite-carbon composite material used for the negative electrode of the lithium-ion battery adopts the following raw materials: 40 g of expanded graphite, 18 g of silicon powder with an average particle size of 30 nanometers, 42 g of sodium carboxymethyl cellulose, and 0.3 g of hexadecyltrimethylammonium bromide.

[0061] Example 5

[0062] The only difference between this embodiment and embodiment 1 is that the silicon-graphite-carbon composite material used for the negative electrode of the lithium-ion battery adopts the following raw materials: 50 g of expanded graphite, 15 g of silicon powder with an average particle size of 30 nanometers, 35 g of sodium carboxymethyl cellulose, and 0.3 g of hexadecyltrimethylammonium bromide.

[0063] Example 6

[0064] The only difference between this embodiment and Embodiment 1 is that the average particle size of the silicon powder is 80 nanometers.

[0065] Example 7

[0066] The only difference between this embodiment and Embodiment 1 is that the average particle size of the silicon powder is 120 nanometers.

[0067] Example 8

[0068] The only difference between this embodiment and embodiment 1 is that cellulose is replaced by an equal amount of sucrose.

[0069] Example 9

[0070] The difference between this embodiment and embodiment 1 is that sodium carboxymethyl cellulose is replaced by an equal amount of starch.

[0071] Example 10

[0072] The only difference between this embodiment and embodiment 1 is that the sodium carboxymethyl cellulose is replaced by an equal amount of a mixture of natural rubber and urea in a weight ratio of 10:1.3.

[0073] Embodiment 11

[0074] The only difference between this embodiment and embodiment 1 is that the sodium carboxymethyl cellulose is replaced by an equal amount of a mixture of natural rubber and urea in a weight ratio of 10:0.3.

[0075] Example 12

[0076] The only difference between this embodiment and embodiment 1 is that the sodium carboxymethyl cellulose is replaced by an equal amount of a mixture of natural rubber and urea in a weight ratio of 10:0.5.

[0077] Embodiment 13

[0078] The only difference between this embodiment and embodiment 1 is that the sodium carboxymethyl cellulose is replaced by an equal amount of a mixture of natural rubber and urea in a weight ratio of 10:2.

[0079] Embodiment 14

[0080] The only difference between this embodiment and embodiment 1 is that the sodium carboxymethyl cellulose is replaced by an equal amount of a mixture of natural rubber and urea in a weight ratio of 10:2.3.

[0081] Embodiment 15

[0082] The only difference between this embodiment and embodiment 1 is that the sodium carboxymethyl cellulose is replaced by an equal amount of a mixture of natural rubber, urea and lithium bromide in a weight ratio of 10:1.3:0.01.

[0083] Example 16

[0084] The only difference between this embodiment and embodiment 1 is that the sodium carboxymethyl cellulose is replaced by an equal amount of a mixture of natural rubber, urea and lithium bromide in a weight ratio of 10:1.3:0.02.

[0085] Embodiment 17

[0086] The only difference between this embodiment and embodiment 1 is that the sodium carboxymethyl cellulose is replaced by an equal amount of a mixture of natural rubber, urea and lithium bromide in a weight ratio of 10:1.3:0.06.

[0087] Embodiment 18

[0088] The only difference between this embodiment and embodiment 1 is that the sodium carboxymethyl cellulose is replaced by an equal amount of a mixture of natural rubber, urea and lithium bromide in a weight ratio of 10:1.3:0.1.

[0089] Embodiment 19

[0090] The only difference between this embodiment and embodiment 1 is that the sodium carboxymethyl cellulose is replaced by an equal amount of a mixture of natural rubber, urea and lithium bromide in a weight ratio of 10:1.3:0.11.

[0091] Embodiment 20

[0092] The only difference between this embodiment and Embodiment 1 is that in the preparation method of the silicon-graphite-carbon composite material for the negative electrode of a lithium-ion battery, the solid block is transferred to a porcelain boat, placed in a tubular furnace and introduced into an inert atmosphere for heat treatment, the temperature is raised to 250°C at a rate of 1°C / min, and then kept warm for 2 hours, and then raised to 600°C at a rate of 1°C / min, and kept warm for 3.5 hours to obtain the silicon-graphite-carbon composite material.

[0093] Embodiment 21

[0094] The only difference between this embodiment and Embodiment 1 is that, in the preparation method of the silicon-graphite-carbon composite material for the negative electrode of a lithium-ion battery, the solid block is transferred to a porcelain boat, placed in a tubular furnace and introduced into an inert atmosphere for heat treatment, the temperature is raised to 250°C at a rate of 2°C / min, and then kept warm for 2 hours, and then the temperature is raised to 600°C at a rate of 2°C / min, and then kept warm for 3.5 hours to obtain the silicon-graphite-carbon composite material.

[0095] Embodiment 22

[0096] The only difference between this embodiment and Embodiment 1 is that in the preparation method of the silicon-graphite-carbon composite material for the negative electrode of a lithium-ion battery, the solid block is transferred to a porcelain boat, placed in a tubular furnace and introduced into an inert atmosphere for heat treatment, the temperature is raised to 250°C at a rate of 6°C / min, and then kept warm for 2 hours, and then raised to 600°C at a rate of 6°C / min, and kept warm for 3.5 hours to obtain the silicon-graphite-carbon composite material.

[0097] Embodiment 23

[0098] The only difference between this embodiment and Embodiment 1 is that in the preparation method of the silicon-graphite-carbon composite material for the negative electrode of a lithium-ion battery, the solid block is transferred to a porcelain boat, placed in a tubular furnace and introduced into an inert atmosphere for heat treatment, the temperature is raised to 250°C at a rate of 10°C / min, and then kept warm for 2 hours, and then the temperature is raised to 600°C at a rate of 10°C / min, and then kept warm for 3.5 hours to obtain the silicon-graphite-carbon composite material.

[0099] Embodiment 24

[0100] The only difference between this embodiment and Embodiment 1 is that in the preparation method of the silicon-graphite-carbon composite material for the negative electrode of a lithium-ion battery, the solid block is transferred to a porcelain boat, placed in a tubular furnace and introduced into an inert atmosphere for heat treatment, the temperature is raised to 250°C at a rate of 11°C / min, and then kept warm for 2 hours, and then the temperature is raised to 600°C at a rate of 11°C / min, and kept warm for 3.5 hours to obtain the silicon-graphite-carbon composite material.

[0101] Embodiment 25

[0102] The only difference between this embodiment and Embodiment 1 is that in the preparation method of the silicon-graphite-carbon composite material for the negative electrode of a lithium-ion battery, the solid block is transferred to a porcelain boat, placed in a tubular furnace and introduced into an inert atmosphere for heat treatment, the temperature is raised to 200°C at a rate of 5°C / min, and then kept warm for 3 hours, and then the temperature is raised to 550°C at a rate of 5°C / min, and then kept warm for 5 hours to obtain the silicon-graphite-carbon composite material.

[0103] Embodiment 26

[0104] The only difference between this embodiment and Embodiment 1 is that in the preparation method of the silicon-graphite-carbon composite material for the negative electrode of a lithium-ion battery, the solid block is transferred to a porcelain boat, placed in a tubular furnace and introduced into an inert atmosphere for heat treatment, the temperature is raised to 300°C at a rate of 5°C / min, and then kept warm for 1 hour, and then the temperature is raised to 650°C at a rate of 5°C / min, and then kept warm for 2 hours to obtain the silicon-graphite-carbon composite material.

[0105] Embodiment 27

[0106] The only difference between this embodiment and embodiment 1 is that in the preparation method of the silicon graphite carbon negative electrode, the SP-Li conductive agent is replaced by an equal amount of KS-6 conductive agent.

[0107] Embodiment 28

[0108] The only difference between this embodiment and embodiment 1 is that in the preparation method of the silicon graphite carbon negative electrode, an equal amount of SFG-6 is used to replace the SP-Li conductive agent.

[0109] Embodiment 29

[0110] The only difference between this embodiment and embodiment 1 is that in the preparation method of the silicon graphite carbon negative electrode, an equal amount of polyvinylidene fluoride is used to replace aqueous sodium carboxymethyl cellulose.

[0111] Embodiment 30

[0112] The only difference between this embodiment and embodiment 1 is that in the preparation method of the silicon graphite carbon negative electrode, an equal amount of styrene-butadiene rubber is used to replace aqueous sodium carboxymethyl cellulose.

[0113] Comparative Example

[0114] Comparative Example 1

[0115] The only difference between this comparative example and Example 1 is that the silicon-graphite-carbon composite material for the negative electrode of the lithium-ion battery uses the following raw materials: 10 g of expanded graphite, 90 g of silicon powder with an average particle size of 50 nanometers, and 1 g of hexadecyltrimethylammonium bromide.

[0116] Comparative Example 2

[0117] The only difference between this comparative example and Example 1 is that the silicon-graphite-carbon composite material for the negative electrode of the lithium-ion battery uses the following raw materials: 37 g of silicon powder with an average particle size of 50 nanometers, 63 g of sodium carboxymethyl cellulose, and 1 g of hexadecyltrimethylammonium bromide.

[0118] Comparative Example 3

[0119] The only difference between this comparative example and Example 1 is that the silicon-graphite-carbon composite material for the negative electrode of the lithium-ion battery uses the following raw materials: 10 g of expanded graphite, 27 g of silicon powder with an average particle size of 1 micron, 63 g of sodium carboxymethyl cellulose, and 1 g of hexadecyltrimethylammonium bromide.

[0120] Comparative Example 4

[0121] The only difference between this comparative example and Example 1 is that the silicon-graphite-carbon composite material for the negative electrode of the lithium-ion battery uses the following raw materials: 10 g of expanded graphite, 27 g of silicon powder with an average particle size of 20 nanometers, 63 g of sodium carboxymethyl cellulose, and 1 g of hexadecyltrimethylammonium bromide.

[0122] Performance testing

[0123] The following performance tests were performed on the silicon-graphite carbon negative electrodes prepared in Examples 1-30 and Comparative Examples 1-4:

[0124] The obtained silicon graphite carbon negative electrode was placed in a glove box filled with argon protection, a metal round lithium sheet with a diameter of 16 mm was used as the counter electrode, Celgard2325 polypropylene film was selected as the diaphragm, 1 mol / L LiPF6 / (EC:EMC:DEC) was selected as the electrolyte, wherein the volume ratio of EC (ethylene carbonate):EMC (methyl vinyl carbonate):DEC (diethyl carbonate) was 1:1:1, and a CR2032 button battery was assembled in a vacuum glove box.

[0125] The first charge and discharge capacity, first coulombic efficiency, reversible specific capacity after 50 cycles and capacity retention rate after 50 cycles of the CR2032 button battery were tested, and the test results are shown in Table 1.

[0126] Table 1

[0127]

[0128]

[0129] Combining Example 1 and Comparative Examples 1-4 and Table 1, it can be seen that compared with Comparative Examples 1-4, the first charge and discharge capacity, the first coulomb efficiency, the reversible specific capacity after 50 cycles and the capacity retention rate after 50 cycles of Example 1 are all significantly larger. The increase in the first charge and discharge capacity helps to improve the service life of the battery. The greater the first coulomb efficiency, the higher the efficiency of converting the chemical energy of the battery into electrical energy. The greater the reversible specific capacity and capacity retention rate after 50 cycles, the greater the battery can maintain longer stability and longer service life during the charge and discharge process. This shows that the use of the raw material ratio of Example 1 helps to improve the durability of the negative electrode material of the lithium ion battery.

[0130] It can be seen from Examples 1-9 and Table 1 that Examples 1-9 all have relatively high initial charge and discharge capacity, initial coulombic efficiency, reversible specific capacity after 50 cycles, and capacity retention rate after 50 cycles. This shows that the raw material ratio ranges of Examples 1-9 are all helpful to improve the durability of the negative electrode material of lithium ion batteries.

[0131] Combining Examples 1, 10-19 and Table 1, it can be seen that the first charge and discharge capacity, the first coulomb efficiency, the reversible specific capacity after 50 cycles and the capacity retention rate after 50 cycles of Examples 10-19 are all larger than those of Example 1. This shows that using a mixture of natural rubber, urea and lithium bromide as an organic carbon source can help further improve the durability of the negative electrode material of lithium ion batteries.

[0132] It can be seen from Examples 1, 20-30 and Table 1 that compared with Example 1, the first charge and discharge capacity, the first coulombic efficiency, the reversible specific capacity after 50 cycles and the capacity retention rate after 50 cycles of Examples 20-30 do not change much, which shows that within the process conditions of Examples 20-30, it is helpful to improve the durability of the negative electrode material of the lithium ion battery.

[0133] Figure 1 is the first charge and discharge capacity diagram of the CR2032 button battery assembled with the negative electrodes of Examples 1-5, Figure 2 It is a graph of the 50-cycle reversible specific capacity of the CR2032 button-type battery assembled with the negative electrodes of Examples 1-5. Figure 3 It is the AC impedance spectrum of the CR2032 button battery assembled with the negative electrodes of Examples 1-5 after 50 cycles. Figure 4 This is a SEM image of the silicon-graphite-carbon composite material for a negative electrode of a lithium-ion battery of Example 1.

[0134] from Figure 1 It can be seen that the potential slope platform of the first discharge curve of the battery assembled by the negative electrode of Examples 1-5 is between 0.1V and 1V, which is caused by the SEI film formed on the surface of the composite material during the discharge process. The potential platform between 0.01-0.1V is the generation of alloy phase between silicon and lithium. In the charging curve, 0.01V-0.2V is mainly the delithiation process of graphite, and the charging process between 0.4V-0.8V corresponds to the delithiation potential of silicon, and the charging platform appears at around 0.5V. The lithium-ion battery prepared in Example 3 has the highest first discharge specific capacity, reaching 1194mAh / g, but its first coulombic efficiency is the lowest, at 62.40%, and as the silicon content decreases, its first coulombic efficiency becomes higher and higher.

[0135] from Figure 2 and Figure 3 It can be seen that after 50 cycles, the reversible specific capacity of the battery assembled with the negative electrode of Example 1 is the largest, which is 495 mAh / g, and the capacity retention rate is also relatively high, which is 80.05%, which is a relatively ideal silicon-based negative electrode material. The charge transfer impedance values ​​of the batteries assembled with the negative electrodes of Examples 1-5 are in the following order from small to large: Example 1 < Example 5 < Example 4 < Example 2 < Example 3.

[0136] Combination Figure 4 It can be seen that the reason for this phenomenon may be due to the addition of expanded graphite. Due to the pore structure on the surface of expanded graphite, nano silicon powder can be well dispersed on the surface of expanded graphite during stirring. At the same time, the carbon shell formed by high-temperature pyrolysis of amorphous carbon is also well coated on the surface of expanded graphite and silicon powder, providing sufficient buffer space for the volume expansion of silicon, so it has good cycle stability.

[0137] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A silicon-graphite-carbon composite material for a negative electrode of a lithium-ion battery, characterized in that: The invention comprises the following raw materials in parts by weight: 10-50 parts of expanded graphite, 15-27 parts of silicon powder with an average particle size of 30-120 nanometers, 35-63 parts of an organic carbon source and 0.3-1 part of a surfactant.

2. The silicon-graphite-carbon composite material for a negative electrode of a lithium-ion battery according to claim 1, characterized in that: The organic carbon source is one or a combination of sucrose, starch or cellulose.

3. The silicon-graphite-carbon composite material for a negative electrode of a lithium-ion battery according to claim 1, characterized in that: The organic carbon source comprises natural rubber and urea in a weight ratio of 10:(0.5-2).

4. The silicon-graphite-carbon composite material for a negative electrode of a lithium-ion battery according to claim 3, characterized in that: The organic carbon source also includes lithium bromide, and the weight ratio of the natural rubber to the lithium bromide is 10:(0.02-0.1).

5. The method for preparing a silicon-graphite-carbon negative electrode according to claim 1, characterized in that: The silicon-graphite-carbon composite material for the negative electrode of a lithium-ion battery comprises a porous carbon skeleton network structure, silicon powder particles and a carbon shell layer, wherein the silicon powder particles are embedded in the porous carbon skeleton network structure, and the carbon shell layer is wrapped around the porous carbon skeleton network structure and the surface of the silicon powder particles.

6. A method for preparing a silicon-graphite-carbon composite material for a negative electrode of a lithium-ion battery according to any one of claims 1 to 5, characterized in that: The steps include: Primary mixing: adding silicon powder, organic carbon source and surfactant into water and mixing evenly to obtain raw material liquid; Secondary mixing: adding expanded graphite to ethanol, mixing evenly to obtain a graphite solution, ultrasonically dispersing the graphite solution, and then mixing evenly with the raw material solution to obtain a mixed solution; Drying: heating the mixed liquid to remove water and ethanol from the mixed liquid to obtain a mixed solid, and drying the mixed solid to obtain a solid block; Heat treatment: heat the solid block to 200-300°C in an inert atmosphere, keep it warm for 1-3 hours, heat it to 550-650°C, keep it warm for 2-5 hours, and obtain a silicon-graphite-carbon composite material.

7. The method for preparing a silicon-graphite-carbon composite material for a negative electrode of a lithium-ion battery according to claim 6, characterized in that: In the heat treatment step, the heating rate is 2-10°C / min.

8. A method for preparing a silicon-graphite-carbon negative electrode, characterized in that: The steps include: Mixing the conductive agent with the silicon-graphite-carbon composite material according to any one of claims 1 to 5 to obtain a conductive mixture, dissolving the binder in N-methylpyrrolidone to obtain a binder solution, and uniformly mixing the conductive mixture and the binder solution to obtain a slurry; The slurry is coated on a copper foil, dried, stamped, compacted, weighed and dried again to obtain a silicon-graphite-carbon negative electrode.

9. The method for preparing a silicon-graphite-carbon negative electrode according to claim 8, characterized in that: The conductive agent is a SP-Li conductive agent.

10. The method for preparing a silicon-graphite-carbon negative electrode according to claim 8, characterized in that: The binder is polyvinylidene fluoride, aqueous sodium carboxymethyl cellulose or styrene-butadiene rubber.